Self-Control in Adolescent: A Systematic Literature Review - Mayangsari, Agnes; Sugiharto, DYP; Mulawarman, Mulawarman (Jurnal Wahana Konseling, 2024)
This study aims to explore various forms of self-control behavior in adolescents. These factors influence the formation of self-control in adolescents and offer psychological intervention strategies that can be carried out in order to improve self-control in adolescents. This study is a type of systematic literature review research, which is a literature review using systematic and structured procedures. The literature search in this study resulted in six kinds of articles from four databases. The results of the literature review produced a number of information related to the form of self-control behavior in adolescents, both low self-control and high self-control. Furthermore, the factors that influence the formation of self-control in adolescents are also known, both from intrinsic and extrinsic factors. In relation to the variety of self-control behaviors that are very important for adolescents to have, a number of psychological intervention strategies were explored to improve self-control in adolescents, namely through the Top-Down Toolbox (TDT), Cognitive and Emotional Resilience Through Somatic Awareness (CERSA), Self-Control Training (SCT) and Mindfulness in Schools Project (MiSP). The results of this study can be used as a reference to help adolescents improve self-control, as well as the basis for implementing further research.